2007
DOI: 10.1161/strokeaha.106.478495
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity in the Access of Elderly Patients to Acute Stroke Care

Abstract: MD; for the Arbeitsgruppe Schlaganfall HessenBackground and Purpose-Sex differences in the management of acute coronary symptoms are well documented. We sought to determine whether sex disparities exist in acute stroke management, particularly with regard to early hospital admission and thrombolytic therapy. Methods-We analyzed a prospective, countywide, hospital-based stroke registry. Between 1999 and 2005, all cases with a final diagnosis of cerebral infarction (ICD-10 I63) or intracerebral hemorrhage (ICD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
1
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 23 publications
5
99
1
1
Order By: Relevance
“…25 Poststroke depression is more common in women than in men, 26 and this hinders functional recovery.…”
Section: Resultsmentioning
confidence: 99%
“…25 Poststroke depression is more common in women than in men, 26 and this hinders functional recovery.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that women are less likely than men to receive care on an acute stroke unit. 19 A number of studies have shown that women hospitalized after a stroke undergo fewer diagnostic procedures than men 15,20 and are less likely to receive thrombolytic treatment 20,21 ; however, these factors could not explain our findings. In addition, there is evidence of an increased admission threshold in women, especially elderly women.…”
Section: Case-fatalitymentioning
confidence: 68%
“…Subsequent analysis identified a large German registry-based study as being influential because of its large size and the fact that it found no evidence of a sex disparity (ORϭ0.97). 11 After removing this study, the analysis of the remaining 3 studies resulted in a marginally significant OR of 0.67; the magnitude of this OR suggested that a substantial sex disparity remains after taking into account patient eligibility. Given the potential for differences in the administration of IV rt-PA between different health care delivery systems, we also conducted a subgroup analysis based on geographic location.…”
Section: Discussionmentioning
confidence: 97%